Minocycline hydrochloride entrapped biomimetic nanofibrous substitutes for adipose derived stem cells differentiation into osteogenesis - Jayaraman, Praveena (2016)
Hybrid biocomposite nanofibrous structures that mimics native extracellular matrix have been extensively applied for bone tissue engineering (BTE) due to their potential in efficiently inducing cellular response for the secretion of extracellular matrix (ECM). This study performed fabrication of uniform porous polycaprolactone (PCL), polycaprolactone/silk fibroin (PCL/SF), polycaprolactone/silk fibroin/minocycline hydrochloride (PCL/SF/MH), polycaprolactone/collagen (PCL/COL), and polycaprolactone/collagen/minocycline hydrochloride (PCL/COL/MH) biocomposites nanofibrous scaffolds by electrospinning, for comparing their properties to use in bone tissue regeneration. Field emission scanning electron microscopy (FESEM) images of fabricated nanofibrous scaffolds revealed porous, beadless, uniform fibers of diameter in the range of 147.13 ± 28.02 to 176.53 ± 22.34 nm and porosity around 82–93 %. Adipose-derived stem cells (ADSCs) considered as the novel cell therapeutics were cultured on these electrospun fibrous scaffolds to undergo osteogenic differentiation for BTE. The cell morphology, proliferation, and interactions were analyzed by CMFDA dye extrusion, MTS assay, and FESEM analysis, respectively. Differentiation of ADSCs into osteogenesis was determined by alkaline phosphatase activity, mineralization by alizarin red staining, and osteogenic protein expression by immunofluorescence analysis. The results demonstrated that the addition of SF and MH to PCL-based scaffolds improved the mechanical stability, interconnected pores, and surface roughness of the scaffolds initiating heightened biological functions such as ADSCs adhesion, proliferation, differentiation, and mineralization into osteogenesis for bone tissue regeneration.